INTERVIEW OF CHIEF EDITOR OF SCIENTIFIC AND TECHNICAL JOURNAL «CASTING AND METALLURGY», CHAIRMAN OF COUNCIL OF BELORUSSIAN PUBLIC ASSOCIATION OF FOUNDERS AND METALLURGISTS, LAUREATE OF STATE-PRIZE OF RB, DOCTOR OF TECHNICAL SCIENCES, PROFESSOR D. M. KUKUJ WITH DIRECTOR OF GO «BELVTORMET» A. V. BOGDANOV - D. M. Kukuj; A. V. Bogdanov (Литьë и металлургия)
.